2016
DOI: 10.1097/id.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dental Implants in Organ Transplant Patients Undergoing Immunosuppressive Therapy

Abstract: Despite the negative impact of immunosuppressive drugs on the process of bone healing, it is possible to treat organ transplant patients with intraosseous titanium implants. The key to success is the observance of appropriate treatment procedures and proper hygienic routines. An alteration of medication regimen that currently makes use of immunosuppressive drugs of much lower toxicity is also extremely significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…Most of these patient have numerous teeth extracted before transplantation because the chronic renal failure and dialysis results in the exacerbation of dental caries indices, aggressive periodontitis, dry mouth and xerostomia, and in preparation for transplantation procedures, the patients must have all potential sources of inflammation removed (12,13). But the use of 3, 6, 12, 24, and 36 months after loading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these patient have numerous teeth extracted before transplantation because the chronic renal failure and dialysis results in the exacerbation of dental caries indices, aggressive periodontitis, dry mouth and xerostomia, and in preparation for transplantation procedures, the patients must have all potential sources of inflammation removed (12,13). But the use of 3, 6, 12, 24, and 36 months after loading.…”
Section: Discussionmentioning
confidence: 99%
“…Also in preparation for transplantation procedures, the patients must have all potential sources of inflammation removed, so in the course of dental treatment, most often to heal the oral cavity, they have numerous teeth extracted, thus leading to vast denture losses, and after successful transplantation they need to rehabilitate their masticatory system (12). That is why the replacement of missing teeth with the use of dental implants would be of such great importance, and at the same time only a few studies on this topic have been reported, with all of them showing the dental implant success rates in transplant patients to be similar to those in healthy subjects (1,2,11,12). The following case report describes the placement of dental implants in a kidney transplant patient.…”
Section: Introductionmentioning
confidence: 99%
“…In respect to the type of transplant recipients included in this study, several types of transplants were included, two on liver [27], one on renal [28], and two with mixed transplant types [31,32]. Overall, these results account for the most prevalent types (renal and liver transplantation) (WHO, 2016), but also the infrequent cases.…”
Section: Quality Of the Evidence Limitations And Potential Biases Imentioning
confidence: 99%
“…Un consentimiento informado no es suficiente para cubrir la responsabilidad al fuero y el pundonor por una programación relajada y mal aconsejada que puede poner en peligro la salud general del paciente. Es imprudente e innecesario programar implantes en franca contravía con factores de riesgo y aspectos co-mórbidos estomatognáticos y sistémicos: bruxismo, enfermedad degenerativa articular, periodontopatías, xerostomía, jóvenes en crecimiento (adolescencia), envejecimiento (adulto mayor), riesgo a endocarditis, quimioterapia, riesgo a osteoradionecrosis, epilepsia, hipotiroidismo, enfermedades mucosas, accidente cerebro vascular, trasplantes (inmunosupresión), hemofilia, trombocitopenia, diabetes e hipertensión descompensadas, diabetes mellitus, trastornos de coagulación, terapia hormonal sustitutiva (bifosfonatos por osteonecrosis), enfermedades autoinmunes, osteoporosis y otras enfermedades óseas, enfermedad hepática o renal avanzada, inmunodeprimidos, fumadores crónicos, alérgicos al titanio, abuso de drogas, alcoholismo, desórdenes neuropsiquiátricos, entre otros (Zadik et al, 2012;Katyayan et al, 2013;Chrcanovic et al, 2014;Gómez-de Diego et al, 2014;Guillaume;Yadav et al, 2016;Radzewski & Osmola, 2016). Hwang & Wang (2006;2007), clasifican las contraindicaciones médicas para estas terapias como absolutas y relativas, mismas que deberían ser tomadas de forma inaplazable por los operadores.…”
Section: "Para Engañar a Los Demás Hay Que Mostrarse Convincenteyunclassified